Martin Bridge in high gear! - Kerrin, Jessica Scott (Kids Can Press, 2008)
Martin's back in two more stories. For their science fair project, Martin's team is going to help save the planet by organizing a beach walk. In the second story, Martin learns what it takes to score an A+ in teamwork and puts his knowledge of tools to good use as a volunteer at Bicycle Recycle.